Sustainable Urban Waste Management Strategies Based on System Dynamics in Manado City, North Sulawesi, Indonesia - Suriandjo, Hendrik; Sinsuw, Alicia Amelia Elizabeth; Chu, Chen-Yeon; Sangkertadi; Waani, Judy Obet; Lahamendu, Verry (International Journal of Integrated Engineering, 2026)
Urban waste management poses significant challenges amid increasing urbanization and limited infrastructure capacity. This study investigates sustainable waste management strategies at the Sumompo Landfill in Manado using the Environmental Risk Index (ERI) and System Dynamics (SD) modeling approaches. The ERI results yielded a total score of 605.9, categorizing the site as high risk, with strong recommendations for landfill closure and environmental remediation. A community survey revealed that 100% of respondents supported the closure, and 45% reported health issues over the past three years attributed to the landfill. SD simulations were developed under three scenarios: pessimistic, moderate, and optimistic. In the optimistic scenario, household waste sorting through waste banks and composting increased to 50%, and daily waste collection was optimized to twice per day. Under this scenario, the total waste volume entering the landfill in 2030 is projected at 986.198 m³, significantly lower than the 1.775.157 m³ projected under the Business As Usual (BAU). For comparison, the 2025 baseline volume is 292.841 m³. The study proposes six integrated strategies, including source level waste reduction, community engagement, institutional reform, and alternative financing. The findings highlight the critical importance of systemic and participatory approaches in achieving resilient and sustainable urban waste management.